Assessment of rates of recanting and hair testing as a biological measure of drug use in a general population sample of young people. - Taylor, Michelle; Sullivan, John; Ring, Susan M.; Macleod, John; Hickman, Matthew (Addiction, 2017)
Aims We investigate the extent of and factors associated with denial of previously reported cannabis and other illicit drug use, and assess the potential of hair testing for measuring substance use in general population samples. Design Birth cohort study. Setting United Kingdom, 1991-present. Participants A total of 3643 participants who provided hair and self-report measures of cannabis and other illicit drug use in the Avon Longitudinal Study of Parents and Children (ALSPAC) at age 18 years. Measurements Denial of ever use of cannabis and other illicit drugs at age 18 following previously reported use. Positive hair drug tests for cannabis and other illicit drugs, and expected numbers of false positives and false negatives based on expected sensitivity and specificity. Findings Cannabis and other illicit drug use was reported by 1223 and 393 individuals, respectively, before age 18 years. Of these 176 (14.4%) and 99 (25.2%), respectively, denied use at age 18. Denial of cannabis use decreased with the reporting of other substances and antisocial behaviour. Cannabis and other illicit drug use at age 18 was reported by 547 (22.5%) and 203 (8.4%) individuals, respectively. Of these, 111 (20.3%) and 13 (6.4%) were hair-positive for cannabis and other illicit drugs, respectively. Based on hair testing for cannabis use we expect 0 [95% confidence interval (CI) = 0-169] false positives and 394 (95% CI = 323-449) false negatives compared to observed 362 potential false positives and 436 potential false negatives based on self-report. In hair-positive individuals, reporting the use of other substances and antisocial behaviour decreased the odds of a negative self-report. Conclusions Hair analysis provides an unreliable marker of substance use in general population samples. People who report more frequent substance use before age 18 are less likely to later deny previous substance use at age 18 than people who report occasional use.